Sosialisasi dan Pendampingan Pengembangan Instrumen Hasil Belajar Berbasis Ketrampilan Berpikir Tingkat Tinggi (HOTS) pada Mahasiswa Magister Pendidikan IPA Universitas Mataram - Wildan Wildan; Aliefman Hakim; Dwi Laksmiwati; Lalu Rudyat Telly Savalas; Supriadi Supriadi (Jurnal Pengabdian Magister Pendidikan IPA, 2019)
Abstract: The objective of this community service activity was to increase the understanding and ability of the students of Master of Science Education University of Mataram to develop learning outcomes instruments based on higher-order thinking skills. This activity was carried out with several methods, namely lectures, questions and answers, brief exercises and focused discussions. The activity ended with an evaluation to get an overview of the process and results of the activity. Data collection was done through questionnaires, interviews, and discussions. Based on the results of data collection, it can be concluded that the activities ran well, the results were very beneficial for the participants, and will be followed up with exercises to develop HOTS-based learning outcomes tests suitable with the demands of the 2013 curriculum. The obstacles in developing HOTS-based learning outcome include inadequate abilities and heavy administrative and academic tasks. Keywords:Science Learning, Learning Outcome, HOTS